Reader Response Analysis In Bridging Literature And Learning Through Billy Collins' Introduction To Poetry - Pratiwi, Cysakaren Diva (University of Brawijaya, 2024)
This study investigates the effectiveness of utilizing Billy Collins' poem Introduction to Poetry as a pedagogical tool to cultivate reader response and critical thinking skills in the context of literature and education. By conducting a qualitative analysis of students' interpretations and reactions, the research aims to elucidate how poetry can facilitate connections between personal experience and academic analysis. Data were collected through student surveys and reflective essays, revealing that engagement with the poem through the lens of reader-response theory significantly helped students bridge the gap between personal meaning-making and academic interpretation. The findings suggest that such engagement not only fosters a deeper connection to the text but also enhances students' critical thinking and emotional literacy. Many students demonstrated improved abilities to analyze the poem critically while also reflecting on their emotional responses, confirming that poetry can promote more individualized and reflective learning outcomes. Furthermore, this study explores the broader pedagogical role of literature in education, with findings indicating that literature, particularly poetry, plays a vital role in developing students' critical thinking and self-reflection skills. Overall, the integration of poetry into the curriculum demonstrates its pedagogical significance in fostering both intellectual and emotional growth in students.